ANALYSIS OF EARNINGS GROWTH, DIVIDEND POLICY, CONSERVATISM, TAX AGGRESSIVENESS ON CORPORATE EARNINGS QUALITY - Azzahra, Fadia; Afiqoh, Nyimas Wardatul (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Financial statements are an important source of information for evaluating the financial position and performance of a company. This report contains information about the company's profit, which makes it possible to measure success or failure in achieving predetermined goals. This study aims to examine the effect of growth, dividend policy, conservatism, and tax aggressiveness on the quality of corporate earnings. The research sample consists of mining sector companies in Indonesia listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023, using purposive sampling technique and using 34 company sample from mining sector. The results showed that dividend policy and tax aggressiveness have a significant influence on the quality of corporate earnings. Effective dividend policy and appropriate tax aggressiveness practices can improve the quality of corporate earnings. On the other hand, earnings growth and conservatism do not show a significant effect on earnings quality. This indicates that increased profits do not always reflect good financial performance, and prudent principles in financial reporting do not always correlate with improved earnings quality